Biosynthesis of the Nitrile Glucosides Rhodiocyanoside A and D and the Cyanogenic Glucosides Lotaustralin and Linamarin in Lotus japonicus - Forslund, Karin (American Society of Plant Biologists, 2004)
Lotus japonicus was shown to contain the two nitrile glucosides rhodiocyanoside A and rhodiocyanoside D as well as the cyanogenic glucosides linamarin and lotaustralin. The content of cyanogenic and nitrile glucosides in L. japonicus depends on plant developmental stage and tissue. The cyanide potential is highest in young seedlings and in apical leaves of mature plants. Roots and seeds are acyanogenic. Biosynthetic studies using radioisotopes demonstrated that lotaustralin, rhodiocyanoside A, and rhodiocyanoside D are derived from the amino acid l-Ile, whereas linamarin is derived from Val. In silico homology searches identified two cytochromes P450 designated CYP79D3 and CYP79D4 in L. japonicus. The two cytochromes P450 are 94% identical at the amino acid level and both catalyze the conversion of Val and Ile to the corresponding aldoximes in biosynthesis of cyanogenic glucosides and nitrile glucosides in L. japonicus. CYP79D3 and CYP79D4 are differentially expressed. CYP79D3 is exclusively expressed in aerial parts and CYP79D4 in roots. Recombinantly expressed CYP79D3 and CYP79D4 in yeast cells showed higher catalytic efficiency with l-Ile as substrate than with l-Val, in agreement with lotaustralin and rhodiocyanoside A and D being the major cyanogenic and nitrile glucosides in L. japonicus. Ectopic expression of CYP79D2 from cassava (Manihot esculenta Crantz.) in L. japonicus resulted in a 5- to 20-fold increase of linamarin content, whereas the relative amounts of lotaustralin and rhodiocyanoside A/D were unaltered.